Lathi: Ekspresi Resistensi Ataukah Komodifikasi Mitos (Analisis Semiotik Dalam Video Klip “Lathi”) - Farida M. Arif; Amir S. Kiwang (Jurnal Kewarganegaraan, 2023)
Abstract Music video as a product of popular culture were used to express feeling or as struggling sites of ideology. “Lathi” is a one kind of it. This video carries the theme of women’s resistance while the discrimination of women always happening. The aim of this research is to describe how Lathi represented women’s resistance and the ideologies behind it. This qualitative-descriptive type research used representation theory, and commodification theory to analyzing how women struggle to gain emancipation on popular culture. Semiotic was used in this research as analysis method, that inspired by Carol Vernalis. Data analysis divided into three sections: (1) describing structures of music video, (2) describing chronologies, (3) and from those two sections, being associated with women’s ressistance and commodification. The results shows that women have double repression, not just patriarki but also capitalism spesifically comodification. Women are again described as weak and cannot be equal to men. Even if that women becomes strong, it’s a magical and illogical power. Keyword: Lathi, Woman Resistance, Magical Power, Commodification